2023
DOI: 10.3390/su15043667
|View full text |Cite
|
Sign up to set email alerts
|

Pollution and Risk Evaluation of Toxic Metals and Metalloid in Water Resources of San Jose, Occidental Mindoro, Philippines

Abstract: Clean and safe drinking water is an integral part of daily living and is considered as a basic human need. Hence, this study investigated the suitability of the domestic water (DW) and groundwater (GW) samples with respect to the presence of metals and metalloid (MMs) in San Jose, Occidental Mindoro, Philippines. The MMs analyzed in the area of study for DW and GW were Arsenic (As), Barium (Ba), Copper (Cu), Chromium (Cr), Iron (Fe), Lead (Pb), Manganese (Mn), Nickel (Ni), and Zinc (Zn). The results revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 131 publications
0
1
0
Order By: Relevance
“…The new model, as a result of calibration to adjust default calibration values and meet site specific factors, has been labelled as ‘soil ziploc mode’. After this, the portable XRF is ready for elemental analysis and becomes a reliable instrument for metal detection in this study for various media, and it has been used in various studies [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. The 77 samples were analyzed for the presence of ten (10) metals, such as arsenic (As), barium (Ba), cadmium (Cd), copper (Cu), iron (Fe), lead (Pb), manganese (Mn), mercury (Hg), nickel (Ni), and zinc (Zn).…”
Section: Methodsmentioning
confidence: 99%
“…The new model, as a result of calibration to adjust default calibration values and meet site specific factors, has been labelled as ‘soil ziploc mode’. After this, the portable XRF is ready for elemental analysis and becomes a reliable instrument for metal detection in this study for various media, and it has been used in various studies [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. The 77 samples were analyzed for the presence of ten (10) metals, such as arsenic (As), barium (Ba), cadmium (Cd), copper (Cu), iron (Fe), lead (Pb), manganese (Mn), mercury (Hg), nickel (Ni), and zinc (Zn).…”
Section: Methodsmentioning
confidence: 99%
“…The XRF device was extremely beneficial for measuring soil Mn as the study site is on a remote island without an appropriate analytical laboratory. It can analyze metal concentrations in soil samples, though the focus of this study is Mn, with a confidence level of 99.7% [51] and has been employed for a range of environmental monitoring studies [52][53][54].…”
Section: Soil and Surface Water Sampling In Mogpog And Boac Municipal...mentioning
confidence: 99%
“…In addition, several industries, such as those using electroplating and copper mining processes generate wastewater with (II) concentrations that are way above the toxic concentrations [2]. This increase in heavy metals found in water is alarming due to the adverse effects of heavy metals if ingested [3]. Furthermore, it has also been found that around half of Filipinos depend on groundwater as their primary source of drinking water [4].…”
Section: Introductionmentioning
confidence: 99%